Preparation method of low-cost high-magnification silicon-carbon secondary particle negative electrode material

By coating and spray drying and granulating alumina on silicon carbon materials, a tightly connected alumina network is formed, which solves the problem of attenuation of the kinetic performance of existing silicon carbon composite materials and achieves efficient lithium ion transmission and fast charging performance.

CN119601573APending Publication Date: 2025-03-11XUANCHENG SILIKO NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411698899.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing silicon-carbon composite materials have attenuation in terms of dynamic performance, especially under low SOC conditions, which cannot meet the fast charging needs of new energy power batteries. At the same time, the binding force and integrity of the alumina coating method are insufficient.

Method used

Fine-powder porous carbon is used as raw material, silicon carbon material is deposited through the rotary furnace method, and heat treatment is carried out with the aluminum powder to form an alumina cladding layer. Then, the alumina ion channel is further constructed through spray drying and granulation technology to form a tightly connected alumina network.

Benefits of technology

It significantly improves the dynamic performance of the material, improves the transmission rate of lithium ions, enhances the fast charging performance of the material, and reduces the lithium-embedded expansion of silicon carbon particles by reserving space, improving the circulation stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601573A_ABST
    Figure CN119601573A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of negative electrode materials, in particular to a preparation method of a low-cost and high-rate silicon-carbon secondary particle negative electrode material. The method comprises the following steps: step 1, using fine powder porous carbon; 2, performing vapor deposition to obtain a silicon carbon material; step 3, preparing a silicon carbon material partially coated with aluminum oxide; step 4, dispersing the silicon carbon material partially coated with aluminum oxide in an aluminum salt solution to obtain a first mixed slurry, and adding urea into the first mixed slurry to obtain a second mixed slurry; 5, carrying out spray drying granulation on the secondary mixed slurry to obtain secondary particles; and sixthly, heat treatment is conducted. According to the method, fine powder waste in the CVD silicon carbon production process is recycled, so that the production cost is reduced; aluminum oxide is synthesized in situ on the surface of the silicon-carbon material, an aluminum oxide ion channel is constructed through spray drying, the silicon-carbon material and aluminum oxide are tightly connected, the transmission rate of lithium ions in the surface interface of the material is improved, and the fast charging performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrode materials, and in particular to a method for preparing a low-cost and high-rate silicon-carbon secondary particle negative electrode material. Background Art

[0002] With the development of new energy fields, especially the widespread application of electric vehicles and energy storage systems, power batteries, as their core components, have increasingly higher requirements for energy density and power density. In order to meet these requirements, the research on negative electrode materials has become a hot topic, among which silicon (Si) is considered to be one of the most promising candidates for the next generation of negative electrode materials due to its theoretical specific capacity of up to 4200mAh / g. However, silicon undergoes a huge volume expansion during the charging and discharging process (up to more than 300%), which can lead to the rupture of electrode materials and the rapid decay of battery performance. In addition, the high conductivity of silicon also limits its performance in practical applications.

[0003] In order to overcome the above problems, the scientific research community and the industry have developed a variety of silicon-based composite materials. Among them, silicon-carbon (Si-C) composite materials have received widespread attention due to their high structural stability and synergistic effects. China Patent Announcement No.: CN117577819A has developed a silicon-carbon composite negative electrode material and its preparation method and application. This highly tightly composite structure greatly improves the circulation and expansion of silicon negative electrode materials, but it has been found that the kinetics of this material is significantly attenuated compared with traditional nano-silicon materials. Although the scientific research community and the industry are still unclear about the deterioration mechanism of its kinetics, it can be identified that the lithium ion transmission resistance of this silicon-carbon material is large, and this deterioration is particularly obvious at low SOC, which cannot meet the current fast charging needs of new energy power batteries. For this reason, China Patent Announcement No.: CN117613209A proposes an alumina-coated silicon-carbon material and its preparation method and application, which improves the kinetics of silicon-carbon materials to a certain extent, but this coating method is too simple to guarantee the bonding force between alumina and silicon-carbon, as well as the integrity of the alumina layer.

[0004] In view of this, a method for preparing a silicon-carbon secondary particle negative electrode material with low cost and high rate is provided to solve the problems of the prior art. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a silicon-carbon secondary particle negative electrode material with low cost and high rate, so as to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides a method for preparing a low-cost and high-rate silicon-carbon secondary particle negative electrode material, comprising the following steps:

[0007] Step 1: Use fine powder porous carbon with Dv50-2μm and Dn10-0.1μm, put it into a rotary kiln, introduce nitrogen, the nitrogen flow rate is 5L / min, evacuate until the oxygen content of the tail gas is less than 100ppm, reduce the nitrogen flow rate to 1L / min, raise the temperature to 450℃ at 5℃ / min, keep warm for 30min, introduce 2L / min monosilane (SiH4) into the rotary kiln cavity, use nitrogen as carrier gas, and set the whole flow rate to 10L / min; preferably, the concentration of monosilane is 5-95%, and the introduction time is 300min;

[0008] Step 2: The rotary furnace is heated to 600-800°C, acetylene is turned on, the acetylene flow rate is 1L / min, and vapor deposition is performed for 2h to obtain a silicon-carbon material;

[0009] Step 3: Mix the silicon-carbon material and aluminum powder, with the aluminum powder added in an amount of 1-3wt%, and heat treat at 250-450°C for 2-8h to obtain a silicon-carbon material partially coated with aluminum oxide. In this step, the silicon oxide on the surface of the silicon-carbon is fixed with aluminum oxide in advance, which can improve the integrity of the subsequent aluminum oxide coating, increase the bonding force between the aluminum oxide layer and the silicon-carbon, and optimize the cycle and rate of the silicon-carbon.

[0010] Step 4: The silicon-carbon material partially coated with alumina is dispersed in an aluminum salt solution with a volume mass parameter of 5-40% by high-speed stirring to obtain a first mixed slurry with a solid content of 7-20%, and then urea with a molar number of 3 times that of the aluminum salt solution is added thereto, and the solid content is controlled at 5-15% by stirring and mixing to obtain a second mixed slurry;

[0011] Step 5: granulate the second mixed slurry by spray drying, with a liquid flow rate of 3-6 L / min, a gas inlet temperature of 120-160°C, an outlet temperature of 90-110°C, and a pressure of 1.5-2.8 kg / cm; obtain secondary particles;

[0012] Step 6: Heat-treat the secondary particles in a box furnace at 300-500°C for 3-6 hours, and cool to room temperature to obtain the final alumina-coated silicon-carbon secondary particles. In this step, heat treatment is performed at 300-500°C to generate an alumina coating layer, further increase the surface stability, and provide mechanical support to alleviate the lithium-insertion expansion of the silicon-carbon particles.

[0013] In the present invention, silicon-carbon material and aluminum powder are pre-reacted to generate a partial aluminum oxide layer (primary reaction), and then the aluminum oxide layer introduced by spray drying is tightly fitted (secondary reaction) to form a tightly connected and loose aluminum oxide network, which greatly improves the dynamic properties of the material; secondly, due to the introduction of spray drying, volume space for silicon expansion is reserved, and the compaction density of the material is 0.5-0.9g / cc. It is worth mentioning that the conventional compaction density of silicon-carbon is above 0.9g / cc. The introduction of spray drying reduces the compaction density, which means that there is more reserved space inside the particles to alleviate volume expansion.

[0014] As a further improvement of the technical solution, the fine powder porous carbon adopts fine powder waste in the CVD silicon carbon production process.

[0015] As a further improvement of the technical solution, the microporosity of the fine powder porous carbon is 80-99%, and the pore volume is 0.5-1.2cm 3 / g.

[0016] As a further improvement of the technical solution, the aluminum salt solution adopts one of aluminum chloride and aluminum nitrate, preferably aluminum nitrate.

[0017] As a further improvement of the technical solution, the aluminum powder is aluminum oxide.

[0018] As a further improvement of the technical solution, the purity of the aluminum powder is 99.5%.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] In the preparation method of this low-cost and high-rate silicon-carbon secondary particle negative electrode material, fine powder waste in the CVD silicon-carbon production process is reused, which reduces production costs; alumina is synthesized in situ on the surface of the silicon-carbon material and alumina ion channels are constructed by spray drying, so that the silicon-carbon material and alumina are tightly connected, thereby improving the transmission rate of lithium ions in the material surface interface and enhancing the fast charging performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the effect of temperature change on heat treatment of secondary particles in an embodiment of the present invention;

[0022] Figure 2 Schematic diagram of the effect of capacity and mass change of aluminum nitrate in an embodiment of the present invention. DETAILED DESCRIPTION

[0023] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] according to Figure 1 As shown, the embodiment of the present invention provides a method for preparing a low-cost and high-rate silicon-carbon secondary particle negative electrode material, comprising the following steps:

[0026] Step 1: Use fine powder porous carbon with Dv50-2μm, Dn10-0.1μm (microporosity 90%, pore volume 0.85cm 3 / g), take 800g and put it into a rotary kiln, introduce nitrogen, the nitrogen flow rate is 5L / min, evacuate until the oxygen content of the tail gas is less than 100ppm, reduce the nitrogen flow rate to 1L / min, heat to 450℃ at 5℃ / min, keep warm for 30min, introduce 2L / min of monosilane (SiH4) into the rotary kiln cavity, use nitrogen as carrier gas, and set the whole flow rate to 10L / min; keep for 300min;

[0027] Step 2: The rotary furnace is heated to 600°C, acetylene is turned on, the acetylene flow rate is 1L / min, and vapor deposition is performed for 2h to obtain a silicon-carbon material;

[0028] Step 3: Mix the silicon-carbon material and aluminum powder (99.5%), with the aluminum powder added in an amount of 1 wt%, and heat treat at 300° C. for 3 h to obtain a silicon-carbon material partially coated with aluminum oxide;

[0029] Step 4: Disperse the silicon-carbon material partially coated with alumina in 1.5L of aluminum nitrate solution (the volumetric mass parameter of aluminum nitrate is 20%) by high-speed stirring, dilute with water to obtain a first mixed slurry, the solid content of which is controlled at 10%, and then add urea with a molar number of 3 times that of the aluminum nitrate solution, the solid content of which is controlled at 12%, and stir and mix to obtain a second mixed slurry;

[0030] Step 5: The second mixed slurry is granulated by spray drying, with a liquid flow rate of 5 L / min, a gas inlet temperature of 130°C, an outlet temperature of 100°C, and a pressure of 2.0 kg / cm. Secondary particles are obtained;

[0031] Step 6: Place the secondary particles in a box-type furnace for heat treatment at 300°C for 3 hours, then cool to room temperature to obtain the final alumina-coated silicon-carbon secondary particles.

[0032] Example 2

[0033] Compared with Example 1, this embodiment deletes the content of step 3, and the rest is the same as Example 1, specifically including the following steps:

[0034] Step 1: Use fine powder porous carbon with Dv50-2μm, Dn10-0.1μm (microporosity 90%, pore volume 0.85cm 3 / g), take 800g and put it into a rotary kiln, introduce nitrogen, the nitrogen flow rate is 5L / min, evacuate until the oxygen content of the tail gas is less than 100ppm, reduce the nitrogen flow rate to 1L / min, heat to 450℃ at 5℃ / min, keep warm for 30min, introduce 2L / min of monosilane (SiH4) into the rotary kiln cavity, use nitrogen as carrier gas, and set the whole flow rate to 10L / min; keep for 300min;

[0035] Step 2: The rotary furnace is heated to 600°C, acetylene is turned on, the acetylene flow rate is 1L / min, and vapor deposition is performed for 2h to obtain a silicon-carbon material;

[0036] Step 3: Disperse the silicon-carbon material in 1.5L aluminum nitrate solution (the volumetric mass parameter of aluminum nitrate is 20%) by high-speed stirring, dilute with water to obtain the first mixed slurry, the solid content of which is controlled at 10%, and then add urea with a molar number of 3 times that of the aluminum nitrate solution, the solid content of which is controlled at 12%, and stir and mix to obtain the second mixed slurry;

[0037] Step 4: The second mixed slurry is granulated by spray drying, with a liquid flow rate of 5 L / min, a gas inlet temperature of 130°C, an outlet temperature of 100°C, and a pressure of 2.0 kg / cm. Secondary particles are obtained;

[0038] Step 5: Place the secondary particles in a box-type furnace for heat treatment at 300°C for 3 hours, then cool to room temperature to obtain the final alumina-coated silicon-carbon secondary particles.

[0039] Example 3

[0040] Compared with Example 1, the heat treatment temperature in step six of this embodiment is modified to 400° C. The remaining steps are the same as those of Example 1 and will not be described in detail in this embodiment.

[0041] Example 4

[0042] Compared with Example 1, the heat treatment temperature in step six of this embodiment is modified to 500° C. The remaining steps are the same as those of Example 1 and will not be described in detail in this embodiment.

[0043] Example 5

[0044] Compared with Example 1, the capacity mass fraction of aluminum nitrate in step 4 is modified to 10%, and the remaining steps are the same as those in Example 1, which will not be described in detail in this example.

[0045] Example 6

[0046] Compared with Example 1, the capacity mass fraction of aluminum nitrate in step 4 is modified to 30%, and the remaining steps are the same as those in Example 1, which will not be described in detail in this example.

[0047] Comparative Example 1

[0048] Compared with Example 1, step 3, step 4, step 5 and step 6 are deleted in this example, and the remaining steps are the same as those in Example 1, which will not be described in detail in this comparative example.

[0049] Comparative Example 2

[0050] Compared with Example 1, the heat treatment temperature in step six of this example is modified to 600° C. The remaining steps are the same as those of Example 1 and will not be described in detail in this comparative example.

[0051] Comparative Example 3

[0052] Compared with Example 1, the capacity mass fraction of aluminum nitrate in step 4 is modified to 60%, and the remaining steps are the same as those in Example 1, which will not be described in detail in this comparative example.

[0053] Table 1 Amount of each raw material used in Examples 1-5 (parts)

[0054]

[0055] As shown in Table 1, the 1.5V capacity, 1.5V first efficiency and each cycle retention rate of the negative electrode materials provided in Examples 1-6 of the present invention are relatively stable and high, indicating that the silicon-carbon secondary particle negative electrode material prepared in the examples of the present invention has good performance;

[0056] Since steps 3 to 6 are omitted in Comparative Example 1, its performance is reduced, especially the buckle electrical expansion rate after 100 cycles is significantly higher than that of Examples 1-6;

[0057] In Comparative Example 2, the heat treatment temperature of step 6 was modified, and its performance decreased at the 1.5V first efficiency, and other indicators were similar to those of the embodiment;

[0058] Comparative Example 3 modifies the concentration of aluminum nitrate in step 4. Although the first efficiency at 1.5 V is similar to that of the embodiment, the cycle retention rate is generally lower than that of the embodiment.

[0059] Secondly, according to Figure 1As shown, in combination with Example 1, Example 3 and Example 4, in step six, the heat treatment temperature is between 300-500°C. The higher the reaction temperature, the denser the generated alumina coating layer, which can provide more lithium ion migration channels for the silicon-carbon surface and increase the surface stability. Alumina can provide mechanical support to alleviate the lithium insertion expansion of silicon-carbon particles, and the capacity retention rate and rate performance of the corresponding materials are optimized. However, after the reaction temperature exceeds 500°C, the first effect of the silicon-carbon material will decrease, so it is necessary to balance the first effect loss and expansion gain. For example, after the temperature is raised to 600°C in Comparative Example 2, the first effect is greatly reduced, but because the alumina is already completely coated at 500°C, further increasing the temperature cannot obtain new expansion and rate performance benefits. Therefore, it can be explained that the heat treatment temperature of 300-500°C in step six is ​​an important factor affecting the silicon-carbon material to obtain new expansion and rate performance benefits.

[0060] In addition, according to Figure 2 As shown, in combination with Example 1, Example 5 and Example 6, when the capacity quality parameter of aluminum nitrate is reduced in Example 5, the rate and expansion of silicon carbon are reduced compared with Example 1. This is because the coating is incomplete due to insufficient alumina. Example 6 increases the capacity quality parameter of aluminum nitrate. Since alumina does not contribute to the capacity, the capacity of the silicon-carbon shell is reduced. Since the alumina coating is more complete, its rate and expansion are slightly improved compared with Example 1; however, Comparative Example 3 further increases the capacity quality parameter of aluminum nitrate, but the result is no further benefits of expansion and circulation, but a large amount of capacity is lost. Therefore, it can be explained that the capacity quality parameter of aluminum nitrate of 3-40% is an important factor affecting the expansion and further benefits of silicon-carbon materials.

[0061] Furthermore, the performance indicators of Examples 1 to 6 are relatively stable and perform well, especially Example 1, which shows the best results in all performance indicators. Specifically, the 1.5V capacity of Example 1 is 1750mAh / g, the 1.5V first efficiency is 91.5%, the capacity retention rate of 100 cycles at 1C is 98.5%, the capacity retention rate of 100 cycles at 3C is 96.0%, the capacity retention rate of 100 cycles at 6C is 89.1%, and the buckling expansion rate after 100 cycles is 15.6%.

[0062] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a low-cost and high-rate silicon-carbon secondary particle negative electrode material, characterized in that: The following steps are involved: Step 1: Use fine powder porous carbon, put it into a rotary kiln, introduce nitrogen and then heat it, then introduce monosilane into the rotary kiln cavity, using nitrogen as carrier gas; Step 2: heating the rotary kiln, opening acetylene, and vapor deposition to obtain silicon-carbon material; Step 3: Mix the silicon-carbon material and alumina, add 1-3 wt % aluminum powder, and obtain a silicon-carbon material partially coated with alumina after heat treatment; Step 4: Disperse the silicon-carbon material partially coated with alumina in an aluminum salt solution with a volume mass parameter of 5-40% by high-speed stirring to obtain a first mixed slurry, and then add urea in a mole number that is 3 times that of the aluminum salt solution, and stir and mix to obtain a second mixed slurry; Step 5, granulating the second mixed slurry by spray drying to obtain secondary particles; Step 6: Place the secondary particles in a box-type furnace for heat treatment and cool to room temperature to obtain the final alumina-coated silicon-carbon secondary particles.

2. The method for preparing a low-cost and high-rate silicon-carbon secondary particle negative electrode material according to claim 1, characterized in that: The fine powder porous carbon is made of fine powder waste in the production process of CVD silicon carbon.

3. The method for preparing a low-cost and high-rate silicon-carbon secondary particle negative electrode material according to claim 1 or 2, characterized in that: The fine powder porous carbon has a microporosity of 80-99% and a pore volume of 0.5-1.2 cm 3 / g.

4. The method for preparing a low-cost and high-rate silicon-carbon secondary particle negative electrode material according to claim 1, characterized in that: In the step 1, the nitrogen flow rate is 5 L / min, and the exhaust is carried out until the oxygen content of the tail gas is less than 100 ppm. The nitrogen flow rate is reduced to 1 L / min, the temperature is raised to 450° C., and the temperature is kept for 30 minutes. The monosilane is introduced at 2 L / min, and the whole flow rate is set to 10 L / min. The monosilane concentration is 5-95%, and the introduction time is 300 minutes.

5. The method for preparing the low-cost and high-rate silicon-carbon secondary particle negative electrode material according to claim 4, characterized in that: In the step 2, the rotary furnace is heated to 600-800° C., acetylene is turned on, the acetylene flow rate is 1 L / min, and the vapor deposition is performed for 2 hours.

6. The method for preparing the low-cost and high-rate silicon-carbon secondary particle negative electrode material according to claim 1, characterized in that: In the step three, the heat treatment temperature is 250-450° C., and the heat treatment time is 2-8 hours.

7. The method for preparing a low-cost and high-rate silicon-carbon secondary particle negative electrode material according to claim 1, characterized in that: In the step 4, the solid content of the first mixed slurry is 7-20%, and the solid content of the second mixed slurry is 5-15%.

8. The method for preparing a low-cost and high-rate silicon-carbon secondary particle negative electrode material according to claim 1, characterized in that: In the step 5, spray drying is performed, the liquid flow rate is 3-6 L / min, the gas inlet temperature is 120-160° C., the outlet temperature is 90-110° C., and the pressure is 1.5-2.8 kg / cm.

9. The method for preparing a low-cost and high-rate silicon-carbon secondary particle negative electrode material according to claim 1, characterized in that: In the step six, the heat treatment temperature is 300-500° C. and the heat preservation time is 3-6 hours.

10. The method for preparing a low-cost and high-rate silicon-carbon secondary particle negative electrode material according to claim 1, characterized in that: The aluminum salt solution is one of aluminum chloride and aluminum nitrate.

Citation Information

Patent Citations

  • Silicon-carbon composite negative electrode material and preparation method and application thereof

    CN117577819A

  • Alumina-coated silicon carbon material and preparation method and application thereof

    CN117613209A